2010
DOI: 10.1186/1748-717x-5-12
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Sorafenib following combined therapy of three-dimensional conformal radiation therapy/intensity-modulated radiation therapy and transcatheter arterial chemoembolization in patients with locally advanced hepatocellular carcinoma: a phase I/II study

Abstract: BackgroundThree-dimensional conformal radiation therapy (3DCRT)/intensity-modulated radiation therapy (IMRT) combined with or without transcatheter arterial chemoembolization (TACE) for locally advanced hepatocellular carcinoma (HCC) has shown favorable outcomes in local control and survival of locally advanced HCC. However, intra-hepatic spreading and metastasis are still the predominant treatment failure patterns. Sorafenib is a multikinase inhibitor with effects against tumor proliferation and angiogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…A Chinese study of advanced-stage HCC (32) obtained promising results for the combination of sorafenib with chemoembolization compared with chemoembolization alone, and a recent study that used propensity-score methods (22) also revealed that the addition of chemoembolization to sorafenib had an impressive effect on tumor progression in these patients. An interesting phase I/II study (33) showed that maintenance therapy with sorafenib after combined treatment with RT and chemoembolization was well tolerated. The therapeutical benefit of chemoembolization plus RT in our hands may encourage other investigators to evaluate the clinical efficacy of this combination for HCC with portal invasion.…”
Section: Discussionmentioning
confidence: 98%
“…A Chinese study of advanced-stage HCC (32) obtained promising results for the combination of sorafenib with chemoembolization compared with chemoembolization alone, and a recent study that used propensity-score methods (22) also revealed that the addition of chemoembolization to sorafenib had an impressive effect on tumor progression in these patients. An interesting phase I/II study (33) showed that maintenance therapy with sorafenib after combined treatment with RT and chemoembolization was well tolerated. The therapeutical benefit of chemoembolization plus RT in our hands may encourage other investigators to evaluate the clinical efficacy of this combination for HCC with portal invasion.…”
Section: Discussionmentioning
confidence: 98%
“…In many cancers, nuclear factor kappa B (NF-κB) is involved in tumor initiation and progression mediated via STAT3 activation [3638]. Inflammatory cytokines induced by NF-κB pathway activation might affect angiogenesis directly via endothelial cells, or indirectly by cancer cells or recruitment and/or activation of inflammatory cells [3946]. Interleukin (IL)-1α has a critical role by recruitment of inflammatory cells [47, 48].…”
Section: Tablementioning
confidence: 99%
“…SF is a commonly used single agent with modest antitumor activity and safety in patients with HCC [11,12] and has been used in numerous combination chemotherapy protocols [13,14]. It has been shown that SF administrated after radiotherapy can prevent or delay the intrahepatic and extrahepatic spreading of HCC, which provides the rationale for the combination of these treatment modalities [15]. Thus, Lopez et al [1] have suggested that future studies should assess the benefits of combined molecular therapy, as opposed to SF treatment alone.…”
Section: Introductionmentioning
confidence: 99%